Network Management Automation Through Virtualization - Manasyan, Arusyak D. (Mathematical Problems of Computer Science, 2022)
The study aims to develop methods for automating network management by analyzing its virtual counterpart. The paper substantiates the relevance of this approach, identifies the advantages and disadvantages, highlights the existing problems, and suggests ways to solve them. As a result, the effectiveness of network virtualization was shown by the example of an experimental network.